Bibliometric Analysis of Randomised Controlled Studies Related to Schizophrenia in the Field of Nursing. - Bayrak, Nurten Gulsum (International Journal of Caring Sciences)
Background: Randomised controlled trials are very important because they obtain results that reveal the effectiveness of interventions used by nurses Objective: To determine the research trends of randomised controlled trials published in the field of nursing related to schizophrenia Method: Data were obtained from studies published in the SCOPUS database before 20.08.2024. 'Schizophrenia', 'Nursing', 'Randomised controlled trial' keywords were searched and 34 studies were evaluated and analysed. The science mapping and visualisation software program VOSviewer was used in the analysis of the research. Results: It was found that the first randomised controlled study on the subject was published in 1995, studies were frequently conducted in the United States, Turkey and the United Kingdom, Turkey had the most collaboration, studies were frequently published in the Archives of Psychiatric Nursing journal, and the number of publications tended to decrease after the pandemic. Conclusion: It is recommended to increase publications on schizophrenia in the field of nursing and to make arrangements to increase cooperation between countries.